2010
DOI: 10.1186/1471-2229-10-3
|View full text |Cite
|
Sign up to set email alerts
|

Deep sequencing identifies novel and conserved microRNAs in peanuts (Arachis hypogaeaL.)

Abstract: BackgroundMicroRNAs (miRNAs) are a new class of small, endogenous RNAs that play a regulatory role in the cell by negatively affecting gene expression at the post-transcriptional level. miRNAs have been shown to control numerous genes involved in various biological and metabolic processes. There have been extensive studies on discovering miRNAs and analyzing their functions in model species, such as Arabidopsis and rice. Increasing investigations have been performed on important agricultural crops including so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

48
134
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(184 citation statements)
references
References 57 publications
48
134
2
Order By: Relevance
“…In our data, we found two reads mapping the RNAi-5x insert, in very low abundance, yet, we found consistently low levels of aflatoxin in repeated challenging experiments in one or both transformed lines, particularly in line 288-10. Low copy numbers of sRNAs in peanut has been reported previously [36,37]; where, similar to our study, the majority of the peanut miRNAs had only one copy. Low copy numbers for transgene-derived siRNAs has been reported previously as well: Jahan et al [50] found few and low copy numbers of transgene-derived siRNAs in transgenic potato expressing a hairpin RNA construct targeting the G protein ß-subunit (PiGB1) of Phytophthora infestans, which is an essential gene involved in the pathogenicity of this pathogen.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In our data, we found two reads mapping the RNAi-5x insert, in very low abundance, yet, we found consistently low levels of aflatoxin in repeated challenging experiments in one or both transformed lines, particularly in line 288-10. Low copy numbers of sRNAs in peanut has been reported previously [36,37]; where, similar to our study, the majority of the peanut miRNAs had only one copy. Low copy numbers for transgene-derived siRNAs has been reported previously as well: Jahan et al [50] found few and low copy numbers of transgene-derived siRNAs in transgenic potato expressing a hairpin RNA construct targeting the G protein ß-subunit (PiGB1) of Phytophthora infestans, which is an essential gene involved in the pathogenicity of this pathogen.…”
Section: Discussionsupporting
confidence: 92%
“…In this study a large percentage of the sRNAs had read lengths of 20-24 nucleotides, which is typical for DICER-processed sRNA products [24][25][26]. The size distribution of the sRNAs in peanut is also consistent with previous reports [36,37]. Furthermore, the majority of sRNAs had a uracil or adenine as 5 terminal nucleotide, which suggest preferential loading onto AGO1, and AGO2 and AGO4, respectively [27]; these enzymes have a crucial role in the RNAi process.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Bars = 10 mm. [See online article for color version of this figure. ] nucleotides, while the size of most known miRNAs is 21 nucleotides (Mi et al, 2008;Wu et al, 2009;Zhao et al, 2010). Consistently, small RNAs in our libraries were predominantly 21 and 24 nucleotides ( Fig.…”
Section: Deep-sequencing Analysis Of Small Rna Libraries From M Oryzsupporting
confidence: 85%
“…The prediction of precursor sequences for about 60% of the conserved miRNAs in our analysis was high when compared to previous reports in other species without an available genome sequence such as Arachis hypogaea L., for which precursors of nine conserved miRNA families out of 75 were identified (Zhao et al 2010). These results suggest that the database used in this analysis adequately covers the transcriptome of the studied tissues.…”
Section: Morais Et Al 2013)mentioning
confidence: 42%